PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DI DESA NEGARA NABUNG KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR DALAM PEMBANGUNAN - Department, administratio; Irawan, Rofi; Mersa, Sudarman; Mulyono, Joko (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
ABSTRACT. This article aims to describe community participation in village development. The study was conducted with a descriptive qualitative approach. The results of the study show that in the development there is a sense of belonging between the people. Formed a sense of dependence and attachment (sense of belonging and sense of commitment) to the purpose of life. Created skills to adjust to changing circumstances. There is a real manifestation of village development and the existence of initiatives among community members.